Retinal arterial occlusion with multiple retinal emboli and carotid artery occlusion disease. Haemodynamic changes and pathways of embolism. Issue 1 (27th July 2020) - Chen, San-Ni; Hwang, Jiunn-Feng; Huang, Jeff; Wu, Shey-Lin
Abstract : Objective: To introduce a special subgroup, retinal artery occlusion (RAO) with multiple emboli, which is highly associated with ipsilateral carotid artery occlusion disease (CAOD). Methods and analysis: This is a cohort study. Cases of RAO with multiple retinal emboli were consecutively enrolled. All patients underwent at least one of the carotid/cerebral evaluations: carotid arteriography, orbital/carotid colour Doppler ultrasonography and CT angiography to demonstrate haemodynamic changes and to discuss possible mechanisms and pathways of the emboli. Results: Among 208 RAO eyes, 12 eyes (5.7%) in 11 patients had multiple emboli were recruited in this study. Eleven eyes (91.6%) had ipsilateral carotid plaques and atherosclerosis with high-grade stenosis; among them, five were total carotid occlusion. Haemodynamic changes were found in nine patients with RAO (81.8%) with carotid stenosis 60% or greater. Most compensatory intracranial circulations were re-established via the circle of Willi with antegrade ophthalmic flows, but the direction of ophthalmic flow reversed in three eyes indicating the recruitment of external collaterals. Two cases underwent carotid stent successfully. Conclusion: RAOs with multiple emboli are rare but highly associated with severe CAOD with haemodynamic flow changes, warning critical condition in carotid/cerebral circulations. Either direct embolism from the carotid or cardiac lesions or indirect embolism via the collateral pathways is the mechanism of pathogenesis. Immediate action should start to manage these patients to prevent further deterioration.